2001
DOI: 10.1099/00207713-51-6-2037
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenies of atpD and recA support the small subunit rRNA-based classification of rhizobia.

Abstract: The current classification of the rhizobia (root-nodule symbionts) assigns them to six genera. It is strongly influenced by the small subunit (16S, SSU) rRNA molecular phylogeny, but such single-gene phylogenies may not reflect the evolution of the genome as a whole. To test this, parts of the atpD and recA genes have been sequenced for 25 type strains within the α-Proteobacteria, representing species in Rhizobium, Sinorhizobium, Mesorhizobium, Bradyrhizobium, Azorhizobium, Agrobacterium, Phyllobacterium, Myco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
207
1
9

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(226 citation statements)
references
References 75 publications
9
207
1
9
Order By: Relevance
“…The genes of the atp operon, especially the atpD gene, have all of the prerequisites to be suitable phylogenetic markers, such as very high genetic stability and a wide distribution (22,23). This operon has already been used to infer phylogeny in the genera Salmonella (6) and Rhizobium (13). This alternative molecular marker might corroborate and help complete the evolutionary history of various LAB species.…”
Section: Discussionmentioning
confidence: 91%
“…The genes of the atp operon, especially the atpD gene, have all of the prerequisites to be suitable phylogenetic markers, such as very high genetic stability and a wide distribution (22,23). This operon has already been used to infer phylogeny in the genera Salmonella (6) and Rhizobium (13). This alternative molecular marker might corroborate and help complete the evolutionary history of various LAB species.…”
Section: Discussionmentioning
confidence: 91%
“…Previously, six of them had been partially characterized by ARDRA, SDS-PAGE and 16S rRNA gene sequencing (Zakhia et al, 2004). Genes for MLSA were chosen according to previous taxonomic and phylogenetic studies: recA (recombinase A) and atpD (ATP synthase beta subunit) were used in a phylogenetic study of the genera Agrobacterium and Rhizobium (Gaunt et al, 2001); glnA (glutamine synthase) was used by Turner & Young (2000) and gltA (citrate synthase) was used by Hernandez-Lucas et al (2004). In a study evaluating the taxonomic potential of ten housekeeping genes, Martens et al (2007Martens et al ( , 2008 found these genes and additionally thrC (threonine synthase) useful for identification and for the inference of phylogenetic relationships of species of the genus Ensifer.…”
Section: Discussionmentioning
confidence: 99%
“…Isoprenoid quinones were isolated using the methods of Minnikin et al (1984) and separated by HPLC (Kroppenstedt, 1982). The DNA G+C content of strain K-38 T was 63.5 mol%, well within the range reported for other species of the genus Rhizobium (57-66 mol%; Young et al, 2001). The predominant isoprenoid quinone of strain K-38 T was Q-10, in line with all members of the family Rhizobiaceae (Bibi et al, 2012;Ramana et al, 2013;Turdahon et al, 2013).…”
Section: Characteristic 1 2mentioning
confidence: 99%
“…To further clarify the taxonomic status of strain K-38 T , two housekeeping genes, ATP synthase b (atpD) and DNA recombinase A (recA), were amplified with the corresponding protocols and primer pairs, atpD273F and atpD771R, recA6F and recA555R, respectively (Gaunt et al, 2001). Phylogenetic trees based on atpD and recA genes were reconstructed using the MEGA 4.0 software.…”
Section: Characteristic 1 2mentioning
confidence: 99%